Innovative transcriptome‐based genotyping highlights environmentally responsive genes for phenology, growth and yield in a non‐model grain legume. (23rd September 2020) - Plewiński, Piotr; Ćwiek‐Kupczyńska, Hanna; Rudy, Elżbieta; Bielski, Wojciech; Rychel‐Bielska, Sandra; Stawiński, Stanisław; Barzyk, Paweł; Krajewski, Paweł; Naganowska, Barbara; Wolko, Bogdan; Książkiewicz, Michał
Abstract: The narrow‐leafed lupin, Lupinus angustifolius L., is a grain legume crop, cultivated both as a green manure and as a source of protein for animal feed and human food production. During its domestication process, numerous agronomic traits were improved, however, only two trait‐related genes were identified hitherto, both by linkage mapping. Genome‐wide association studies (GWAS), exploiting genomic sequencing, did not select any novel candidate gene. In the present study, an innovative method of 3′‐end reduced representation transcriptomic profiling, a massive analysis of cDNA ends, has been used for genotyping of 126 L. angustifolius lines surveyed by field phenotyping. Significant genotype × environment interactions were identified for all phenology and yield traits analysed. Principal component analysis of population structure evidenced European domestication bottlenecks, visualized by clustering of breeding materials and cultivars. GWAS provided contribution towards deciphering vernalization pathway in legumes, and, apart from highlighting known domestication loci ( Ku/Julius and mol ), designated novel candidate genes for L. angustifolius traits. Early phenology was associated with genes from vernalization, cold‐responsiveness and phosphatidylinositol signalling pathways whereas high yield with genes controlling photosynthesis performance and abiotic stress (drought or heat) tolerance. PCR‐based toolbox was developed and validated to enable tracking desired alleles in marker‐assisted selection. Narrow‐leafed lupin was genotyped with an innovative method of transcriptome profiling and phenotyped for phenology, growth and yield traits in field. Early phenology was found associated with genes from cold‐response, vernalization and phosphatidylinositol signalling pathways, whereas high yield with genes running photosystem II and drought or heat stress response. Key loci were supplied with PCR‐based toolbox for marker‐assisted selection. Abstract : Narrow‐leafed lupin was genotyped with an innovative method of transcriptome profiling and phenotyped for phenology, growth and yield traits in field. Early phenology was found associated with genes from cold‐response, vernalization and phosphatidylinositol signaling pathways, whereas high yield with genes running photosystem II and drought or heat stress response. Key loci were supplied with PCR‐based toolbox for marker‐assisted selection.